The Last Supper: Art, Faith, Sex, and Controversy in the 1980s: Oleh Paul Elie - Rynaldi Mahardika Situmeang (Indonesian Journal of Theology, 2026)
A book review of The Last Supper: Art, Faith, Sex, and Controversy in the 1980s.